Clinical and research updates on the VISTA immune checkpoint: immuno-oncology themes and highlights - Noelle, Randolph J.; Lines, J. Louise; Lewis, Lionel D.; Martell, Robert E.; Guillaudeux, Thierry; Lee, Sam W.; Mahoney, Kathleen M.; Vesely, Matthew D.; Boyd-Kirkup, Jerome; Nambiar, Dhanya K.; Scott, Andrew M. (Frontiers in Oncology, 2023)
Immune checkpoints limit the activation of the immune system and serve an important homeostatic function but can also restrict immune responses against tumors. Inhibition of specific immune checkpoint proteins such as the B7:CD28 family members programmed cell death protein-1 (PD-1) and cytotoxic T-lymphocyte antigen-4 (CTLA-4) has transformed the treatment of various cancers by promoting the anti-tumor activation of immune cells. In contrast to these effects, the V-domain immunoglobulin suppressor of T-cell activation (VISTA) regulates the steady state of the resting immune system and promotes homeostasis by mechanisms distinct from PD-1 and CTLA-4. The effects of VISTA blockade have been shown to include a decrease in myeloid suppression coupled with proinflammatory changes by mechanisms that are separate and distinct from other immune checkpoint proteins; in some preclinical studies these immune effects appear synergistic. Given the potential benefits of VISTA blockade in the context of cancer therapy, the second Annual VISTA Symposium was convened virtually on September 23, 2022, to review new research from investigators and immuno-oncology experts. Discussions in the meeting extended the knowledge of VISTA biology and the effects of VISTA inhibition, particularly on cells of the myeloid lineage and resting T cells, as three candidate anti-VISTA antibodies are in, or nearing, clinical development.